PENGARUH LIKUIDITAS, SALDO LABA DAN ARUS KAS LABA TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Sri Hermuningsih; Pristin Prima Sari; Anisya Dewi Rahmawati (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
The study aims to investigate a model of likuidity, Retained Earning, Profitability cash Flow influence to firm value listed in Indonesia Stock Exchange 2018-2020 from publication of quartedly financial statement. Liquidity, retained earning and cash flow of profitability called internal source funds. Our study provide pecking order hypothesis which prefer internal source funding to increase firm value. The study uses regression analysis and logit analysis. The beneficial of research such as supporting model of financial contraits and their impact to firm value. The study found that liquidity, retained earning and cash flow of profitability have positive simultaneously significant to firm value, meanwhile liquidity and cash flow of profitability partially have positive significant to firm value at 0,05 significant level and retained earning have partially positive significant at 0,10 level. The results can be used by management to manage financial constrait.